Branch line coupler using hybrid T-model structure - Mohd Tarmizi, Ali, Dr.; Shahrul Kamal, Abdul Rahim, Assoc. Prof. Ir. Dr.; Muhammad Zairil, Muhammad Nor; Mohd Faizal, Jamlos, Dr. (Wiley Periodicals, Inc., 2013)
Link to publisher's homepage at http://onlinelibrary.wiley.com/